Research progress in composition design, microstructure and properties of refractory high entropy alloys - WU Junxia; LI Peiyou; DONG Hongfeng; LIU Yaling; ZHANG Wei; WANG Lin; WANG Yongshan (Journal of Aeronautical Materials, 2022)
High entropy alloy is defined as an alloy containing four or more main elements. The atomic fraction of the main elements is greater than 5% and not more than 35%, which has excellent properties such as high strength, high wear resistance and high corrosion resistance. Refractory high-entropy alloy is a new type of superalloy designed and developed based on high-entropy alloy of refractory elements, which has broad application prospects in aerospace, petrochemical and other fields, and is expected to replace traditional superalloys. This paper reviews the composition design of refractory high-entropy alloys from the aspects of element selection and addition of trace elements, and its phase composition has single-phase structure and duplex structure, and the preparation method and performance characteristics of refractory high-entropy alloys are studied, and finally gives the problems and challenges faced by refractory high entropy alloys. This review provides a valuable reference for researchers in the component design, microstructure regulation and performance development of refractory high entropy alloys.